PERENCANAAN STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI SI/TI PENDIDIK DAN TENAGA KEPENDIDIKAN (Studi Kasus: Pada Disdikbudpora Metro) - Arifani, Irfan Nur; Darmawan, Abdi (244-5567)
The Education, Culture , Youth and Sport Agency of Metro has not got a plan for main implementation for Information System /Information Technology so the information needed cannot be managed accurately. For that reason, it is really needed an IT-based system to produce precise and puctual information. This study is aimed at identifying data needs and information in formulating the policy and developing strategic information system plan in the educational agency. The main concept in designing this study is a methodology stated by John Ward and Joe Peppard. The steps start from analyzing internal business circumtance and external organization, IT internal analysis and it is continued by processing strategic indentification and doing future portofolio design. The analysis methods used in this study include SWOT, Critical Success Factor, Value Chain, PEST, and Mc Fardan Strategic Grid.The result of this study is a stratgic plan blue print which refers to the organization business plan based on the data derived from the analysis method. The information resulted is then to be used as an integrated method for administrative needs and public services. The strategic purpose is a prime service that can be used to increase the data management for maximizing functions of Educators and Educational Officers (PTK). They are supported with IT factors, IT roles to provide the qualified educational infra structures and develop IT application for improving the quality of educational management. The IT strategic plan produced can be used in planning the next strategic plan and give some priorities for activities to find the great results and are based on the aims to achieve.Keywords : Information System Strategic Plan, Ward and Peppard Method